A highly sensitive and selective fluorescent sensor for the determination of copper(II) based on a schiff base - Aksuner, Nur; Henden, Emuer; Yilmaz, Ibrahim; Cukurovali, Alaaddin (Elsevier Sci Ltd, 2009)
A highly sensitive and selective optical sensor for the determination of trace amounts of Cu(2+) based on fluorescence quenching has been developed. The sensing membrane was prepared by immobilization of a novel fluorescent Schiff base ligand 4-(1-phenyl-1-metliylcyclobutane-3-yl)-2-(2-hydroxy-5-romobenzylidene)aminothiazole, on polyvinlyl chloride. The novel sensor, which has a linear range of 1.0 x 10(-8) - 5.7 x 10(-4) mol L(-1) for CU(2+) ions with a detection limit of 8.8 x 10(-9) mol L(-1) (0.56 mu g L(-1)), is fully reversible and the response time (tau(90)) was approximately 2.5 min. The optode was highly selective and can readily be regenerated by treatment with 10(-2) mol L(-1) HCL The accuracy of the proposed sensor was confirmed by analyzing standard reference materials of natural water and peach leaves. The sensor was successfully applied for the determination of copper in tap water and tea samples. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Schiff base; PVC matrix; Fluorescence spectroscopy; Optical sensor; Copper(II); Fluorescence quenching